1997
DOI: 10.1029/97jd00928
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol climatology at the high‐alpine site Jungfraujoch, Switzerland

Abstract: Abstract. Continuous aerosol measurements have been performed at the high-alpine site Jungfraujoch (3450 m above sea level) since 1988 by means of an epiphaniometer. The instrument, which determines the Fuchs surface area of the aerosol particles, was operated with a time resolution of 30 min. High correlation coefficients (r > 0.8) were found between the epiphaniometer signal and other aerosol parameters, which could be attributed to a rather constant size distribution of the Jungfraujoch aerosol in the accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
163
1
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 228 publications
(178 citation statements)
references
References 24 publications
10
163
1
4
Order By: Relevance
“…The JFJ is prevalently situated in the free troposphere, but is influenced by convection of planetary boundary layer air during the warmer months (Baltensperger et al, 1997;Lugauer et al, 1998). Consequently all the measured aerosol parameters show a clear annual cycle with maximum values in July and August and minimum values in the NovemberJanuary period.…”
Section: Methodsmentioning
confidence: 99%
“…The JFJ is prevalently situated in the free troposphere, but is influenced by convection of planetary boundary layer air during the warmer months (Baltensperger et al, 1997;Lugauer et al, 1998). Consequently all the measured aerosol parameters show a clear annual cycle with maximum values in July and August and minimum values in the NovemberJanuary period.…”
Section: Methodsmentioning
confidence: 99%
“…The JFJ site (3580 m asl) is prevalently situated in the lower FT, but is often influenced by thermal convection of PBL air during the warmer months [Baltensperger et al, 1997;Lugauer et al, 1998]. All measured aerosol variables show a clear annual cycle (Figure 1) with maximum values between June and August and minimum values around the winter solstice [Nyeki et al, 1998;M.…”
Section: Measurement Sitementioning
confidence: 99%
“…From 06:00 LT, the concentration of both polarities increase until reaching a maximum of 825 # cm −3 and 875 # cm −3 respectively for negative and positive ions at 13:00 LT. Then the concentrations decrease rapidly from 15:00 to 18:00 LT to reach the level of night time. Baltensperger et al (1997) showed that diurnal variations of aerosol parameters such as surface area are due to thermally driven vertical exchange. In their article, Lugauer et al (2000) have demonstrated that during winter the Jungfraujoch is most of time decoupled from the PBL and, during the summer, air from the PBL is transported to the site by thermally driven convection.…”
Section: Ultrafine Charged Aerosol Climatologymentioning
confidence: 99%